The Eminent Monk: Buddhist Ideals in Medieval Chinese Hagi-ography. John Kieschnick. - Tarocco, Francesca (Buddhist Studies Review, 2019)
The Eminent Monk: Buddhist Ideals in Medieval Chinese Hagi-ography. John Kieschnick. (Studies in East Asian Buddhism 10), University of Hawai’i/Kuroda Institute, Honolulu 1997. vii, 218 pp. ISBN 0-8248-1841-5.